Acetaldehyde Induces Neurotoxicity In Vitro via Oxidative Stress- and Ca2+ Imbalance-Mediated Endoplasmic Reticulum Stress. (9th January 2019) - Cui, Jiahui; Liu, Yang; Chang, Xing; Gou, Wenfeng; Zhou, Xuejiao; Liu, Zi; Li, Zengqiang; Wu, Yingliang; Zuo, Daiying
Abstract : Excessive drinking can damage brain tissue and cause cognitive dysfunction. Studies have found that the early stage of neurodegenerative disease is closely related to heavy drinking. Acetaldehyde (ADE) is the main toxic metabolite of alcohol. However, the exact mechanisms of ADE-induced neurotoxicity are not fully clear. In this article, we studied the cytotoxic effect of ADE in HT22 cells and primary cultured cortical neuronal cells. We found that ADE exhibited cytotoxicities against HT22 cells and primary cultured cortical neuronal cells in dose-dependent manners. Furthermore, ADE induced apoptosis of HT22 cells by upregulating the expression of caspase family proapoptotic proteins. Moreover, ADE treatment could significantly increase the intracellular Ca 2+ and reactive oxygen species (ROS) levels and activate endoplasmic reticulum stress (ERS) in HT22 cells. ADE upregulated ERS-related CHOP expression dose-dependently in primary cultured cortical neuronal cells. In addition, inhibition of ROS with antioxidant N-acetyl-L-cysteine (NAC) reduced the accumulation of ROS and reversed ADE-induced increase of ERS-related protein and apoptosis-related protein levels. Mitigation of ERS with ERS inhibitor 4-PBA obviously suppressed ADE-induced apoptosis and the expression of ERS-related proteins. Therefore, ADE induces neurotoxicity of HT22 cells via oxidative stress- and Ca 2+ imbalance-mediated ERS.